Have we become a template nation? - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2011)
In his commentary, SMU assistant professor of law Eugene Tan observed that last week's three MRT service breakdowns have raised concerns over whether our public transport system is able to cope with the increased commuter load and public expectations. While the road and rail infrastructure has grown significantly in the last few years, doubts now fester as to whether the relevant organisations, the people who run them and the systems and policies, have kept pace.